2010
DOI: 10.1097/mcg.0b013e3181d6bd8e
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal Injection of 0.4% Hydroxypropyl Methylcellulose Facilitates Endoscopic Mucosal Resection of Early Gastrointestinal Tumors

Abstract: HPMC solution (0.4%) provides an effective submucosal fluid cushion and is safe for endoscopic resection of early gastrointestinal neoplastic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Other variants of the technique include the use of 2-channel endoscopes, cap-fitted endoscopes, and band ligation. In addition to saline solution, other submucosal injection solutions include mannitol, sodium hyaluronate, dextrose, glycerol, fibrinogen, and hydroxypropyl methylcellulose (2,15,19,20,21) . EMR has represented a major advance in therapy by allowing the resection of superficial lesions and also allowing the removal of large sessile lesions and laterally spreading tumors (LST).…”
Section: Introductionmentioning
confidence: 99%
“…Other variants of the technique include the use of 2-channel endoscopes, cap-fitted endoscopes, and band ligation. In addition to saline solution, other submucosal injection solutions include mannitol, sodium hyaluronate, dextrose, glycerol, fibrinogen, and hydroxypropyl methylcellulose (2,15,19,20,21) . EMR has represented a major advance in therapy by allowing the resection of superficial lesions and also allowing the removal of large sessile lesions and laterally spreading tumors (LST).…”
Section: Introductionmentioning
confidence: 99%
“…Such an optimal agent for submucosal injection should be cost-effective, readily available, easy to inject and provide a durable cushion with minimal damage of the surrounding tissues at the site of injection. Previous studies have shown that the use of hyaluronic acid, hydroxypropyl methylcellulose or glycerol provides dextrose water, albumin and sodium alginate, and have a lasting elevating effect (6,7,10,11,21,22). A recent study reported that carbon dioxide (CO 2 ) could be a satisfactory submucosal injection agent during ESD (21).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated longer lasting cushions made with various agents including hyaluronic acid (HA), hydroxypropyl methylcellulose (HPMC), succinylated gelatin, glycerol, and a fibrinogen solution. [26][27][28][29][30][31][32] Currently, there are no injection solutions that are specifically approved for EMR by the U.S. Food and Drug Administration; therefore, all solutions mentioned in this document would be considered off-label. A 0.4% solution of HA is approved as an injection solution for Endoscopic mucosal resection submucosal injection in Japan (MucoUp; Johnson & Johnson, Tokyo, Japan) and has been demonstrated to sustain mucosal lifting longer than saline solution, reducing the volume of injection solution necessary to complete an endoscopic resection.…”
Section: Submucosal Injection Solutionsmentioning
confidence: 97%
“…35 HPMC has also been demonstrated to be effective in mucosal lifting for EMR. 29,30,36 HPMC preparations are available in the United States as ophthalmic lubricants and are typically viscous solutions and must be diluted to 0.3% to 0.8% to facilitate injection. The use of succinylated gelatin as a submucosal injection solution for colonic EMR has been demonstrated to facilitate removal of large colonic lesions (>20 mm) in fewer pieces for piecemeal EMR in a randomized, double-blind trial compared with normal saline solution.…”
Section: Submucosal Injection Solutionsmentioning
confidence: 99%